School performance in children with type 1 diabetes - French, Robert (International Journal of Population Data Science, 2018)
Background Childhood onset diabetes has broad cognitive and social effects that are likely to impact on the school experience. In turn, educational outcomes are associated with measures of diabetes related health. Objectives This study models school outcome measures for children with diabetes in comparison to their non-diabetic peers. Methods We use education and diabetes data linked and stored in SAIL databank. We have eight academic cohorts of Welsh administrative education data linked to the register of all children diagnosed with Type 1 diabetes in Wales before the age of 15 (The Brecon Cohort). We model the associations for diabetes with both school absence (sessions missed per year) and educational attainment (using high stakes testing at the end of compulsory schooling), adjusting for individual, school and clinic characteristics and clustering. Data Linkage We discuss our approaches to the challenges of linking the education and diabetes register and outline our proposed solution to the governance challenges of linking diabetes related audit data.